2005
DOI: 10.1002/ijc.21535
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of APAF‐1 in B‐CLL results in poor prognosis in the case of concomitant p53 mutation

Abstract: Apoptosis protease‐activating factor 1 (APAF‐1), a transcriptional target of p53, is a cytosolic adaptor protein that links the mitochondrial apoptosis pathway to the caspase cascade. Here, we aimed to study the impact of APAF‐1 expression levels on cell death induced by anticancer drugs or ionizing irradiation (IR) and disease prognosis in B‐type chronic lymphocytic leukemia (B‐CLL) patients. Samples from 138 patients with B‐CLL were investigated for APAF‐1 expression and p53 mutations. The results were relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
1
12
0
2
Order By: Relevance
“…Indeed, silencing of Apaf-1 protein expression by hypermethylation of the gene promoter has been reported in several human tumors, including malignant melanoma and acute leukemia (Fu et al, 2003). Silencing of Apaf-1 expression in B-cell chronic lymphoblastic leukemia (B-CLL) constitutes a negative prognostic marker in the case of concomitant p53 mutations (Sturm et al, 2006). Jia et al, (2001) reported that Apaf-1 deficiency constitutes a significant mode of resistance to cytochrome c-dependent apoptosis in human leukemia cells.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, silencing of Apaf-1 protein expression by hypermethylation of the gene promoter has been reported in several human tumors, including malignant melanoma and acute leukemia (Fu et al, 2003). Silencing of Apaf-1 expression in B-cell chronic lymphoblastic leukemia (B-CLL) constitutes a negative prognostic marker in the case of concomitant p53 mutations (Sturm et al, 2006). Jia et al, (2001) reported that Apaf-1 deficiency constitutes a significant mode of resistance to cytochrome c-dependent apoptosis in human leukemia cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated a strong relationship between APAF-1 expression and response to chemotherapy and progression or prognosis of many neoplastic diseases such as melanoma, Burkitt lymphoma, chronic lymphoid leukemia, colorectal cancer, and cervical cancer (31)(32)(33)(34)(35). Moreover, hypermethylation of the APAF-1 gene may be an independent prognostic factor in acute lymphoblastic leukemia (36).…”
Section: Discussionmentioning
confidence: 99%
“…The relative amounts of APAF-1 cDNAs with or without the additional COOH-terminal WDR were determined using the specific primers C1, 5'-CAGCTGAT GGAACCTTAAAGC-3' and C2, 5'-GTCTGGTCATCA GAAGATGTC-3' (12), and the following PCR conditions: 33 denaturation cycles of 30 s at 94°C, 50-s annealing at 58°C, and 50-s extension at 72°C, followed by a 5-min APAF-1 isoforms in acute myeloid leukemia www.bjournal.com.br extension at 72°C. In order to ensure that the RT-PCR signal was linear with respect to RNA input, we performed kinetic analysis by varying the number of amplification cycles (25,30,33,35,38) and the amount of cDNA input (0.25, 0.5, 0.75, 1.0, 1.25 µg), considering that the same amount of RNA was reverse-transcribed for each sample (Figure 1). On the basis of this analysis, we used 33 cycles for both pairs of primers and 1 µg cDNA.…”
Section: Rna Extraction Cdna Transcription and Rt-pcr Assaysmentioning
confidence: 99%
“…APAF-1 geno raiška buvo vertinta iRNR lygmenyje, kadangi tyrimais įrodyta teigiama koreliacija tarp APAF-1 iRNR ir baltymo kiekio audinyje [8]. Mūsų tyrimas parodė reikšmingus APAF-1 geno raiškos skirtumus tarp navikinio audinio ir jį supančio sveiko audinio.…”
Section: Rezultatų Aptarimasunclassified